Contribuição ao conhecimento químico de plantas do nordeste do Brasil: Ximenia americana Linn. - Araújo, Mônica Regina Silva de (2007)
This work describes the biological and phytochemical investigation of Ximenia americana (Olacaceae), popularly known in the Brazilian Northeastern as "ameixa da terra", "ameixa do Brasil" "ameixa do mato". According to the literature, several biological activities were reported for this specie including antioxidant, moluscicide, antiseptic and adstringent. However, despite their reported use for medicinal purposes, a literature survey revealed that the phytochemical analysis of X americana have been limited to a few reports. The phytochemical investigation of the trunk, barks and root barks of the ethanol extracts using chromatographic procedures, resulted on the isolation and characterization of 0-sitosterol, 13-sitosterol glicoside, oleanolic acid, 3-oxo-olean-12- en-28-oic acid, and oleanolic acid glycoside. The chemical investigations of trunk barks and roots of hexane extracts resulted on the isolation and characterization of the betulinic acid, stignasten-3-one, 3P-hydroxi- 24-cycloarten-26-oic acid, and the new compounds (2E)-8-(3-furil)-2,5,5-trimethy1-8- oxo-octaen-2-oic acid, and 4,4-dimethyl -1 -methilene-2,3 ,4,4a,9,9a-octahydro-1H-benzo anullene-7-carboxilic. The extracts from X Americana trunk, barks and root bank, and (2E)-8-(3-furil)- 2,5,5-trimethy1-8-oxo-octaen-2-oic acid, and 4,4-d i methy1-1-methilene-2,3,4,4a,9,9aoctahydro-1H-benzo anullene-7-carboxilic were evaluated for their anticolinesterase and antioxidant activities, and exhibited good properties. Structure determinations of the isolated compounds were established by spectroscopic date such as: IV, 1D NMR ('H, 13C and DEPT 1350) and 2D NMR (COSY, HMQC, HMBC and NOESY) and comparison with literature data.